Implementasi Aplikasi Pelatihan Kompetensi Keahlian Tenaga Kerja Siap Pakai Berbasis Web - Narindro, Laser; Deriani, Ni Wayan; Nanik Hendayanti, Ni Putu; Prihandini, Adissa Premia; Raja Mahendra, I Made; Wintara Putra, Gusti Putu; Agung Kristiawan, Dewa Putu (Explore: Jurnal Sistem Informasi dan Telematika (Telekomunikasi, Multimedia dan Informatika), 2024)
This research contains the development of a skills competency-based educational management model for ready-to-use workers using a management information system for the Department of Manpower, Transmigration and Energy DKI Jakarta Province. The aim of this research is to create a web application-based education and training model to assist the performance of the Local Government for reducing unemployment through training provided for ready-to-use workers. Apart from that, the application of this Education and Training management model is also to help training implementers, in this case the Job Training Center which is under the auspices of the DKI Jakarta Provincial DTKTE in mapping, planning and implementing training activities as well as carrying out monitoring related to performance achievements through dashboards. This research methodology uses Research and Development for model development and application with the Unified Theory of Acceptance and Use of Technology research approach. The stages in this skills competency education management are: 1) workforce qualification stage; 2) workforce training planning stage; 3) training registration stage; 4) training implementation stage; and 5) level of work energy absorption. Another hope of this research is to make it easier for the public to register for the required skills competency training.